Here's the question you clicked on:
shayshayglee5
Simplify: –6 – 7(c + 10) A.)64 – 7c B.)–76 – 7c C.)4 – 13c D.)–16 – 13c
-6 -7(c +10) distribute the -7 -6 -7c -70 ======the - 7 makes that a minus even though it says plus since a neg times a pos = a a neg then combine like terms -76-7c
2x + 3(x – 2) – 3(x – 6)
again distribute then collect like terms 2x + 3(x-2) - 3(x-6) 2x+ (3x -6) -3x + 18 the 3x will cancel with -3x 2x-6+18 2x+12
When you have an equation like this with paranthesis ALWAYS use distributive property, then add like terms, then solve for the variable
I didn't know that Thanks Birttany!